Bottom-up and top-down forces shaping caribou forage availability on the Lake Superior coast - Kuchta, Ben (2012)
Woodland caribou (Rangifer tarandus) occupying the Lake Superior Coastal distribution, Ontario, exist in three subpopulations with distinct ranges and demographics. In this study, three ranges are analyzed in terms of summer forage density from bites available to caribou at Pukaskwa National Park, on Michipicoten Island, and on the Slate islands in an attempt to identify whether bottom-up (plant habitat driven) or top-down (herbivore driven) effects are driving the density (g per m2) of 18 coarsely grouped and locally important forage taxa. Crude protein of the 18 taxa was also assessed as a measure of forage quality. Effects on forage density were explored with multiple models, notably sets of predictions comparing dominant overstory taxon, elevation, shrub density, and overstory cover (bottom-up factors), versus slope (accessibility to caribou) and occupation of areas of higher herbivore density on predator refuge islands (top-down factors) as estimators of forage density.